2020
DOI: 10.5194/acp-20-7271-2020
|View full text |Cite
|
Sign up to set email alerts
|

The increasing atmospheric burden of the greenhouse gas sulfur hexafluoride (SF<sub>6</sub>)

Abstract: Abstract. We report a 40-year history of SF6 atmospheric mole fractions measured at the Advanced Global Atmospheric Gases Experiment (AGAGE) monitoring sites, combined with archived air samples, to determine emission estimates from 1978 to 2018. Previously we reported a global emission rate of 7.3±0.6 Gg yr−1 in 2008 and over the past decade emissions have continued to increase by about 24 % to 9.04±0.35 Gg yr−1 in 2018. We show that changing patterns in SF6 consumption from developed (Kyoto Protocol Annex-1) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
106
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(123 citation statements)
references
References 67 publications
13
106
3
1
Order By: Relevance
“…In this work the Numerical Atmospheric dispersion Modelling Environment (NAME) (Jones et al, 2007), a Lagrangian atmospheric transport model developed by the UK Met Office, was used to describe the dilution of emissions from source to measurement location. NAME has been used for this type of work in many studies (Manning et al, 2011;Say et al, 2016;Lunt et al, 2018;Montzka et al, 2018a;White et al, 2019;Ganesan et al, 2020;Say et al, 2021;Fraser et al, 2020) and comprehensive details can be found in Arnold et al (2018). NAME uses a three-dimensional description of the atmosphere as calculated by meteorological models.…”
Section: Atmospheric Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work the Numerical Atmospheric dispersion Modelling Environment (NAME) (Jones et al, 2007), a Lagrangian atmospheric transport model developed by the UK Met Office, was used to describe the dilution of emissions from source to measurement location. NAME has been used for this type of work in many studies (Manning et al, 2011;Say et al, 2016;Lunt et al, 2018;Montzka et al, 2018a;White et al, 2019;Ganesan et al, 2020;Say et al, 2021;Fraser et al, 2020) and comprehensive details can be found in Arnold et al (2018). NAME uses a three-dimensional description of the atmosphere as calculated by meteorological models.…”
Section: Atmospheric Modelmentioning
confidence: 99%
“…InTEM (Manning et al, 2011;Arnold et al, 2018) has been developed over many years and has been applied to many gases and regions, e.g. Bergamaschi et al (2018) and Fraser et al (2020). InTEM is used here to estimate UK emissions using the observations described in Table 2.…”
Section: Inversion Frameworkmentioning
confidence: 99%
“…In recent years, SF 6 has gained importance in the electronics industry as an inert, insulating gas, with 2012 emissions of approximately 9 × 10 9 g/yr, contributing 0.0062 Tg F/yr to the atmosphere (Simmonds et al, 2020). NF 3 is also of increasing use in the electronics industry, where it serves as an etching and cleansing agent for silicon components (Weiss et al, 2008).…”
Section: Anthropogenic Impactsmentioning
confidence: 99%
“…3) Eine im Juni erschienene Studie schätzte den weltweiten Ausstoß im Jahr 2018 auf über 9000 Tonnen. 4 "Die Industrie befindet sich in einer Aufbruchstimmung", sagt Physiker Christian Franck, Professor für Hochspannungstechnik an der ETH Zürich. "Es gibt gute Alternativen, die sich etablieren werden.…”
Section: Klimakillerunclassified